The deductive logical competence of nongraduate Caribbean teachers - Brandon, E. P. (ERIC Documentation Service, 1990)
Data on some aspects of the deductive logical competence of non-graduate teachers in the English-speaking Caribbean, primarily Jamaica, are reported in this document. The teachers sampled were those who sat for entrance examinations for The University of the West Indies (UWI), Mona, Faculty of Education's Bachelor of Education and Certificate of Education programmes from 1985 to 1989. The investigations conducted were based on the extensive work carried out in the United States by Robert Ennis and his associates. Deductive logic studies those situations in which a given set of statements--the premises--necessitates another set, the conclusion; that is, if the premises are true, then the conclusion has to be true also. Six examples of each formally identified logical principle were given to those being tested. Respondents were held to have mastered a principle if they got at least five of the six questions right. Results did not reflect a satisfactory level of elementary reasoning ability. The findings are presented in 11 detailed statistical tables and 3 appendices
Keywords: Non-graduate teachers